Students’ Speaking Anxiety: Ready or Not - Risqi Ekanti Ayuningtyas Palupi (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
Language is the main common field for communication. For that reason, communication skills must take part in learning a language. Speaking is being a part of English lessons in schools today. However, making students speak English is not always easy, and there can be several different reasons it happens. One possible reason is speaking anxiety and its influence on second language acquisition. The study aims to analyze the students’ speaking anxiety when they are in the speaking session. The study is based on literature and contains an interview with the teacher. It is stated that speaking anxiety inhibits students from speaking, which hurts their skills. The research shows that speaking is not the main issue at schools. A reason is that speaking anxiety is not seen as a problem concerning language teaching since it can be considered a social difficulty. In order to enrich speaking in a classroom, it is essential to strive for a joyful atmosphere where every student can feel relaxed and motivated to communicate orally.